TUAN GURU RETEH SYEKH ‘ABDURRAHMAN YA’QUB: Kiprah, Peran, dan Pemikirannya dalam Bidang Pendidikan Islam - Zulkifli M. Nuh; Alimuddin Hassan; Kholil Syu'aib (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This paper would like to explain about the gait, role, and thoughts of Tuan Guru Reteh (TGR) Shaykh 'Abdurrahman Ya'qub in the field of Islamic education. This paper is a result of the search for his innovative thinking in developing Islamic education in the area of Indragiri Hilir Riau Province. Based on the results of these searches can be emphasized several things: first, that TGR. Shaykh 'Abdurrahman Ya'qub has a fairly qualified educational background. Second, that TGR. Shaykh 'Abdurrahman Ya'qub has played a very important, major and dual role in the society, especially in the field of education and dakwah even appointed in the administration of government as the formal leader of religion. Third, that TGR. Shaykh 'Abdurrahman includes productive scholars in the birth of written works. Thus, it is very natural and appropriate for TGR. Shaykh 'Abdurrahman Ya'qub is called a scholar who has authoritative, comprehensive and productive religious knowledge in the Malay-Indragiri region in particular, and the archipelago in general. With these considerations, the title as